Influence Patient Satisfaction Quality of Non-JKN Hospital Clinic - Renaldo, Renaldo; Anggoro, Yudhi; Menik, Kasribening (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
At present, patients as consumers can realize the enormous effect on the existence of health care facilities. Patient satisfaction is now a priority for health care providers. The purpose of this study was to determine the effect of service quality on patient satisfaction. This research is a quantitative descriptive. Data analysis methods used are correlation analysis and regression analysis. Based on the results of testing the hypothesis that can be solved regarding the power response (responsiveness) is the most dominant variable affecting patient satisfaction in KRI Elisa. Empathy also has an interest in patient satisfaction. Based on independent evidence, physical evidence (tangible), approval (reliability), responsiveness (responsiveness), empathy (empathy) and Guarantee (guarantee) significantly influence the satisfaction of KRI Elisa patients. The five variables in the dimensions of service quality contributed together to the contribution variable of (R Square) 52.5% on patient satisfaction. This study resulted in the finding that the simultaneous variable quality of service had a significant effect of 54.5% of patient satisfaction at Elisa's inpatient clinic